A conceptual framework in curatorial practices in new media art in the Malaysian art scene / Daygaret Lembut Daya, Valerie Michael and Muhammad Fauzan Abu Bakar - Daya, Daygaret Lembut; Michael, Valerie; Abu Bakar, Muhammad Fauzan (Faculty of Art and Design, 2024)
In Malaysia, technological devices such as computers were introduced as one of the art mediums to be used in the 1980s. New media art in Malaysia is often equated with electronic art, digital art, video, and media art. Thus, the objective of this paper is to identify the curatorial practices in new media art practice by the curators in the Malaysian art scene. This paper aims to construct a conceptual framework of curatorial practices in the new media art. This conceptual framework aims to highlight the main attributes and factors in curating new media art in Malaysia’s art scene. The method used in this research is the Kawakita Jiro which extracts the keywords related to the curatorial practices through the literature reviews. The result shows that the curatorial practices in new media art disciplinary, application, concept, perception, production, integration, and awareness are the curatorial practices in new media in the Malaysian art scene, and the conceptual framework shows that the interrelation between each attribute of curatorial practices has contributed to facilitating the production of new media art.